Zoés, megalopa e estágios juvenis iniciais de Cryptodromiopsis antillensis (Stimpson, 1858): implicações sobre a monofilia dos Dromiacea (Crustacea: Decapoda: Brachyura) - Franco, Georgia Maria de Oliveira (1998)
The ontogeny of Cryptodromiopsis antillensis (Stimpson, 1858) it was analyzed through literature data (RICE & PROVENZANO, 1966) and observations of the megalopa, juveniles and adults. The megalopa of C. antillensis was redescribed and Evius ruber Moreira, 1912 was considered as synonym of C. antillensis by being of the phase megalopa of this species. The ontogeny of the carapace and the cephalic, thoracic and abdominal appendages it was accompanied separately. Carapace, antennule, antenna, mandible, maxillule, maxilla, first maxiliped, second maxiliped, third maxiliped and pereiopods suffer significant changes until the phase megalopa, when they acquire a similar form the one of the adult. After the phase megalopa these appendages just suffer increment of setae. Already the sternum thoracic, abdomen, telson, pleopods and uropods modify until the adult phase, presenting sexual dimorfism. Pl 1 is absent in the phases zoea and megalopa, just appearing in the juveniles ones. The presence of rudimentary pleopods was observed (Pl 3-Pl 5) in the male specimens of C. antillensis. Cryptodromiopsis. Antillensis, has the ontogenetic pattern of the family Dromiidae. The only species that outrange the Dromiidae pattern is Cryptodromia tuberculata, that presents abbreviated development. Ontogenetic data don't support the monophiletism of Podotremata. The zoea 1 of Dromiidae and the pre-zoea of Dynomenidae are similar. The ontogeny of Homolodromiidae came quite different from that of Dromiidae. The character rudimentary uropods (in a ventral view) in the megalopa phase, separates Homolodromiidae from all other Podotremata. Only one ontogenetic character justifies the Dromiacea sensu GUINOT (1978): antennal exopod developed in the megalopa. The ontogenetic pattern of the Archaeobrachyura sensu GUINOT (1978) was also studied. Ontogenetic data don't support the group of Archaeobrachyura. The following ontogenetic characters diagnoses Homoloidea: 4-6 setae and aesthetasc setae in the protopod of the antennule in the zoea 1; pattern of setae in the base (2, 2, ,2, 3) and in the endopod (1+0, 1+0, 1+0, 2+0, 4+1) of the Mxpl in the zoea 1; endopod of the Mxpl dividido in two articles in the megalopa; pattern of setae in the base (1, 1, 1, 1) of the Mxp2 in the zoea 1. Only one ontogenetic character is common to Raninidae and Cymonomidae: furcated telson.